The differential contribution of the innate immune system to a good pathological response in the breast and axillary lymph nodes induced by neoadjuvant chemotherapy in women with large and locally advanced breast cancers - Kaewkangsadan, Viriya; Verma, Chandan; Eremin, Jennifer M.; Cowley, Gerard P.; Ilyas, Mohammad; Satthaporn, Sukchai; Eremin, Oleg (Hindawi, 2017)
The tumour microenvironment consists of malignant cells, stroma, and immune cells. The role of adaptive immunity in inducing a pathological complete response (pCR) in breast cancer with neoadjuvant chemotherapy (NAC) is well studied. The contribution of innate immunity, however, is poorly documented. Breast tumours and axillary lymph nodes (ALNs) from 33 women with large and locally advanced breast cancers (LLABCs) undergoing NAC were immunohistochemically assessed for tumour-infiltrating macrophages (TIMs: M1 and M2), neutrophils (TINs), and dendritic cells (TIDCs) using labelled antibodies and semiquantitative methods. Patients’ blood neutrophils (n = 108), DCs (mDC1 and pDC), and their costimulatory molecules (n = 30) were also studied. Pathological results were classified as pCR, good (GPR) or poor (PRR). In breast and metastatic ALNs, high levels of CD163+ TIMs were significantly associated with a pCR. In blood, high levels of neutrophils were significantly associated with pCR in metastatic ALNs, whilst the % of mDC1 and pDC and expression of HLA-DR, mDC1 CD40, and CD83 were significantly reduced. NAC significantly reduced tumour DCs but increased blood DCs. PPRs to NAC had significantly reduced HLA-DR, CD40, and CD86 expression. Our study demonstrated novel findings documenting the differential but important contributions of innate immunity to pCRs in patients with LLABCs undergoing NAC.